1992
DOI: 10.1007/bf00172186
|View full text |Cite
|
Sign up to set email alerts
|

Expression in E. coli of the gene encoding phenylalanine ammonia-lyase from Rhodosporidium toruloides

Abstract: The active sites of the enzyme phenylalanine ammonia-lyase (Pal) from Rhodosporidium toruloides contains a dehydroalanine residue that is believed to be essential for catalytic activity. Furthermore, the dehydroalanine is believed to be added post-translationally as part of a prosthetic group covalently attached to the enzyme. Perhaps for this reason no attempts to produce Pal in foreign host cells have been reported. We have inserted the entire uninterupted pal gene from R. toruloides into the Escherichia col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 16 publications
(11 reference statements)
1
14
0
Order By: Relevance
“…To improve PAL activity and production, the entire uninterrupted pal gene from R. toruloides was inserted into the E. coli expression vector pKK223-3. E. coli cells containing this vector synthesized a protein of pal-like activity [5]. The pal gene from R. toruloides was expressed in Saccharomyces cerevisiae (S. cerevisiae) and E. coli by using a bifunctional expression system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To improve PAL activity and production, the entire uninterrupted pal gene from R. toruloides was inserted into the E. coli expression vector pKK223-3. E. coli cells containing this vector synthesized a protein of pal-like activity [5]. The pal gene from R. toruloides was expressed in Saccharomyces cerevisiae (S. cerevisiae) and E. coli by using a bifunctional expression system.…”
Section: Discussionmentioning
confidence: 99%
“…A recombinant strain capable of producing a large amount of PAL is therefore highly desirable in order to improve the production of L-phenylalanine from trans-cinnamic acids. Although many efforts have been made to construct recombinant strains with high PAL activity [5][6][7], few results have been reported that the effects of culturing conditions on production of PAL in recombinant E. coli. A recombinant E. coli strain producing a significant amount of PAL was constructed in our earlier report [7].…”
Section: Introductionmentioning
confidence: 99%
“…Some reports showed that PAL gene from R. toruloides was expressed in E. coli [5,6]. Furthermore, a recombinant E. coli strain producing a significant amount of PAL has been constructed in our earlier report; recombinant PAL activity reached 35 U/g [7].…”
Section: Response Surface Analysis For the Optimization Of The Three mentioning
confidence: 99%
“…A recombinant strain capable of producing a large amount of PAL is therefore highly desirable in order to improve L-phenylalanine from trans-cinnamic acids. Although some efforts have been made to construct recombinant strains with high PAL activity [5,6], the yields of recombinant enzyme obtained were disappointingly low. In terms of large-scale production of PAL for industrial and medical uses, recombinant PAL production needs to be improved substantially.…”
Section: Introductionmentioning
confidence: 98%
“…(i) We used a construct of the PAL gene from Rhodosporidium toruloides (21) under the control of a high-expression promoter and expressed it in a strain of Escherichia coli to obtain large amounts of PAL (22). (ii) We used existing (23) and new strains (C.N.S., J. D. McDonald, and C.R.S.…”
mentioning
confidence: 99%